Children’s and Adults’ Sensitivity to Gricean Maxims and to the Maximize Presupposition Principle - Panzeri, Francesca; Foppolo, Francesca (Frontiers in Psychology, 2021)
Up to age five, children are known to experience difficulties in the derivation of implicitly conveyed content, sticking to literally true, even if underinformative, interpretation of sentences. The computation of implicated meanings is connected to the (apparent or manifest) violation of Gricean conversational maxims. We present a study that tests unmotivated violations of the maxims of Quantity, Relevance and Manner, and of the Maximize Presupposition principle, with a Truth Value Judgment task with three options of response. We tested preschoolers and school-aged children, with adults as controls, to verify at which age these pragmatic rules are recognized, and to see whether there is a difference among these tenets. We found an evolutionary trend, and that in all age groups violations of the maxims of Quantity and of Relation are sanctioned to a higher degree compared to infringements of the Maim of Manner and of the Maximize Presupposition principle. We conjecture that this relates to the effects that the violation of a certain maxim or principle has on the goals of the exchange: listeners are less tolerant with statements that transmit inaccurate or incomplete information, while being more tolerant with those that still permit to understand what has happened.